Performance of Lettuce (Lactuca sativa) Grown under Ultisol Subsoil with Chicken Manure and Dolomite - Viani, Reza Junita Okta; Handajaningsih, Merakati; Suprijono, Eko; Marwanto (Akta Agrosia, 2024)
Lettuce is a horticultural plant with a short harvest time that is a popular vegetable choice for planting in polybags in urban areas. Planting media for cultivating plants in  polybags vary widely. The use of nutrient-poor and acidic subsoil in Ultisols as a planting medium requires additional organic matter and lime that are suitable for the plants. This study evaluated the use of subsoil as a medium for growing lettuce by adding เว็บสล็อต | R4shub chicken manure and dolomite. The Completely Randomized Design was used, which consisted of two factors and 6 replications. The first factor was the dose of chicken manure consisting of: 0 ton/ Ha, 10 tons/Ha (38g /polybag), 20 tons/ Ha (76g/ polybag), and 30 tons/ Ha (115g /polybag). The second factor was the dolomite dose, consisting of no dolomite, 1xAl-exch, and 2xAl-exch. A dose of 20 tons /Ha of chicken manure combined with   1xAl-dd of dolomite increased the growth of plants. The treatment of chicken manure at 20 tons/Ha showed growth and yield of lettuce that were as good as a treatment dose of 30 tons/ Ha. The highest fresh weight (123.05g) was obtained from 30 tons/Ha-chicken manure treatment. The appropriate dose of dolomite for lettuce growth and yield was 1xAl-exch, which resulted in a plant fresh weight of 121.12 g. Subsoil is suitable to be used as a medium for planting lettuce in polybags by adding chicken manure or dolomite.  Keywords: organic matter, marginal soil, leafy vegetable, container veg production